Evaluating the Implementation of the Merdeka Curriculum through Inquiry-Based Learning in English Classes at SMAN 8 Makassar - Lubna Rundangi K. Arafah; Sukardi Weda; Chairil Anwar Korompot (Program Studi Magister Pendidikan Bahasa Inggris, Fakultas Bahasa dan Sastra- Universitas Negeri Makassar., 2025)
This study evaluates the implementation of the Merdeka Curriculum in English language instruction at SMAN 8 Makassar, focusing on the application of Inquiry-Based Learning (IBL). Using a qualitative descriptive approach, data were collected through classroom observations, interviews with one English teacher, and two students with differing academic performance levels. Findings indicate that IBL fosters critical thinking, engagement, and independent learning among students. Both teacher and student perceptions were predominantly positive, though challenges such as limited time and student unfamiliarity with the IBL approach were noted. The study concludes with practical recommendations for enhancing IBL-based English instruction within the framework of the Merdeka Curriculum.